Positive solutions of three-point boundary value problems for higher-order p-Laplacian with infinitely many singularities - Fuyi Xu; Yonghong Wu; Lishan Liu; Yunming Zhou (Discrete Dynamics in Nature and Society)
We study a three-point nonlinear boundary value problem with higher-order p-Laplacian. We show that there exist countable many positive solutions by using the fixed point index theorem for operators in a cone.